1984
DOI: 10.1037/0022-3514.47.4.871
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability and cross-situational consistency of affective, behavioral, and cognitive responses.

Abstract: Consistency and stability of feelings were examined in reports that were completed on 3,512 occasions randomly sampled from the lives of 42 subjects. The stability and consistency of responses depended on the situations, individuals, and responses involved. High degrees of consistency were unusual for single responses, although mean levels of responding tended to be both highly stable and consistent. The consistency and stability of variables covaried, suggesting a connection between the two. Persons who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
204
0
11

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(229 citation statements)
references
References 20 publications
14
204
0
11
Order By: Relevance
“…Research also indicates in subjectively similar situations, behaviours and cognition are also typically similar (Diener & Larsen, 1984), but only to the extent that individuals perceive the situations as being subjectively similar (Furr & Funder, 2004). In other words, when individuals perceive their parenting roles and leadership roles as being similar and requiring similar behaviours, they will typically experience family-to-work enrichment more than individuals who do not find the situations to be similar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research also indicates in subjectively similar situations, behaviours and cognition are also typically similar (Diener & Larsen, 1984), but only to the extent that individuals perceive the situations as being subjectively similar (Furr & Funder, 2004). In other words, when individuals perceive their parenting roles and leadership roles as being similar and requiring similar behaviours, they will typically experience family-to-work enrichment more than individuals who do not find the situations to be similar.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of interrole behavioural congruence has many similarities with cross-situational consistency in personality trait expression. A study conducted by Diener and Larsen (1984) on behavioural consistency across situations suggests that individual behaviours, affect, and cognition tend to be similar across situations that are similar.…”
Section: Interrole Behavioural Congruencementioning
confidence: 99%
“…Even in cases where events were obligatory but perceived to be intrinsically motivating, people tended to rate higher in well-being, attesting to the centrality of perceived response freedom. Diener and Larsen (1984) found that life satisfaction measures were reasonably stable across multiple measurements, but behavioral activity measures were not. More detailed analysis of event-activity relationships are obtainable by the model proposed here.…”
mentioning
confidence: 98%
“…This approach postulates that being active leads to increased happiness. Not all the research supports this notion, however (Diener, 1984;Hoyt, Kaiser, Peters, & Babchuk, 1980), and considerable controversy surrounds the theory. Activity in relation to what would appear to be a critical issue.…”
mentioning
confidence: 99%
“…According to Diener and Larsen (1984), people tend to feel their affects in a stable way. This does not mean that people with high levels of positive affect will not feel negative emotions or vice-versa.…”
mentioning
confidence: 99%